Global drivers of food system (un)sustainability: A multi-country correlation analysis - Béné, Christophe; Fanzo, Jessica; Prager, Steven D.; Achicanoy Estrella, Harold Armando; Mapes, Brendan Robert; Álvarez Toro, Patricia; Bonilla Cedrez, Camila (Public Library of Science, 2020)
At present, our ability to comprehend the dynamics of food systems and the consequences of their rapid ‘transformations’ is limited. In this paper, we propose to address this gap by exploring the interactions between the sustainability of food systems and a set of key drivers at the global scale. For this we compile a metric of 12 key drivers of food system from a globally-representative set of low, middle, and high-income countries and analyze the relationships between these drivers and a composite index that integrates the four key dimensions of food system sustainability, namely: food security & nutrition, environment, social, and economic dimensions. The two metrics highlight the important data gap that characterizes national systems’ statistics—in particular in relation to transformation, transport, retail and distribution. Spearman correlations and Principal Component Analysis are then used to explore associations between levels of sustainability and drivers. With the exception of one economic driver (trade flows in merchandise and services), the majority of the statistically significant correlations found between food system sustainability and drivers appear to be negative. The fact that most of these negative drivers are closely related to the global demographic transition that is currently affecting the world population highlights the magnitude of the challenges ahead. This analysis is the first one that provides quantitative evidence at the global scale about correlations between the four dimensions of sustainability of our food systems and specific drivers.